Dysfunctions of the Immune System and Their Role in the Development of Diseases - Ibragimova Nadiya Sabirovna; Tolibov Asomiddin; Egamov Umidjon; Eshnazarova Rukhshona (Peerian Journals Publishing, 2023)
The article is devoted to the consideration of disorders of the immune system and their role in the development of internal diseases. The work examines the basic mechanisms of immune system dysfunction, as well as the connection between immune system disorders and inflammatory processes and other internal diseases. Clinical manifestations and diagnostic criteria for these diseases are given. Understanding the mechanisms and consequences of immune system disorders is essential for the development of new approaches to the treatment and prevention of internal diseases
Keywords: immune system; autoimmune diseases; immunodeficiency states